2017
DOI: 10.1007/s00216-017-0269-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced solid-phase recombinase polymerase amplification and electrochemical detection

Abstract: Recombinase polymerase amplification (RPA) is an elegant method for the rapid, isothermal amplification of nucleic acids. Here, we elucidate the optimal surface chemistry for rapid and efficient solid-phase RPA, which was fine-tuned in order to obtain a maximum signal-to-noise ratio, defining the optimal DNA probe density, probe-to-lateral spacer ratio (1:0, 1:1, 1:10 and 1:100) and length of a vertical spacer of the probe as well as investigating the effect of different types of lateral spacers. The use of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…7). 68,101,102,[165][166][167] Results suggest that electrochemical detection could be up to 10 5 -fold more sensitive than optical detection (by ELISA). 166 Alternatively, Ng et al 103 and Lau et al 100 RPA in combination with electrochemical detection.…”
Section: Electrochemical Detectionmentioning
confidence: 97%
See 1 more Smart Citation
“…7). 68,101,102,[165][166][167] Results suggest that electrochemical detection could be up to 10 5 -fold more sensitive than optical detection (by ELISA). 166 Alternatively, Ng et al 103 and Lau et al 100 RPA in combination with electrochemical detection.…”
Section: Electrochemical Detectionmentioning
confidence: 97%
“…However, several research groups have studied RPA reaction temperatures that lie outside of the recommended range. 38,44,45,60,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] The largest temperature range was tested between 15°C and 50°C; 62,64,69,70,76 and results indicated the marginal reaction temperature to produce a positive result should be greater than 30°C. [62][63][64]66,67,69,71,74,76,77 However, Sun et al 65 and Poulton and Webster 60 showed that temperature as low as 25°C could still generate a positive signal after RPA amplification and subsequent lateral flow strip detection.…”
Section: Influence Of Temperature and Agitationmentioning
confidence: 99%
“…Several methods have been developed with solid phase amplification with performances usually inferior to that achieved with solution phase amplification [5,27e30,39] as primer accessibility is more restricted impeding amplification efficiency, and future work will need to focus on strategies to decrease amplification time. Efforts to optimise the surface chemistry of the immobilised primers, exploiting vertical and horizontal spacers to enhance solid phase amplification has been reported [40]. To decrease the reaction time and improve the limit of detection, the surface-immobilised primer can also be introduced in the solution phase in an approach termed hemi-nested asymmetric solid-phase amplification [41e43].…”
Section: Solid Phase Rpamentioning
confidence: 99%
“…Label-free optical approaches 18,19 , and enzymatic label-based electrochemical ones with high degree of integration have been reported. 20 However, heat sources are needed for getting detectable signals, which represents an important practical limitation.…”
Section: Introductionmentioning
confidence: 99%